Papilla Vaters Tumor in Elderly: an Interdisciplinary Issue - Eric Daniel Tenda; Murdani Abdullah; Kuntjoro Harimurti; Edy Rizal Wahyudi; Czeresna Heriawan Soejono (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2010)
Tumors of the papilla Vater are very rare. Papilla Vater’s tumors are benign or malignant tumors in the ampulla of Vater and periampullary region. Blockage of ampulla leads to the development of obstructive jaundice; intermittent cholangitis, epigastric discomfort and weight loss. Treatment possibilities include endoscopic ampulectomy, surgical transduodenal excision of tumors of the ampulla and pancreatoduodenectomy (PDE). Prognosis depends on histological typing of the tumor and their clinical stage. We report a case of papilla Vater’s tumor in elderly with comorbidities based on literature review. A 68-year-old female patient was referred for evaluation of intra and extra hepatic bile duct dilatation noted on abdominal ultrasonography. She complained of intermittent epigastric and right upper abdominal pain, with yellowish skin for two months. The laboratory findings showed leukocytosis, hyperbilirubinemia, abnormal liver function test, and high Ca 19-9. An endoscopic retrograde cholangiopancreatography (ERCP) revealed a distal obstruction caused by papilla Vater’s tumor. Abdominal computed tomography (CT) with contrast, revealed a dilated common bile duct and pancreatic duct. The histologic evaluation was highly suggestive for dysplasia. She is now on a schedule for a Whipple procedure. To make a true diagnosis and optimal treatment of papilla Vater’s tumor is multimodal. By doing a comprehensive geriatric assessment, with a careful modality selection, a Whipple procedure can be performed in elderly (65 years) safely. The post operative morbidity and mortality depends on their multi morbidity. Surgical, endoscopic, or radiologic biliary decompression; relief of gastric outlet obstruction; and adequate pain control may improve the quality of life but do not affect overall survival rate. By building a great interdisciplinary teamwork, the quality of life increased as follows.Keywords: papilla Vater tumor, elderly, Whipple procedure